Analisis Unsur Perbuatan Pidana Dalam Kasus Korupsi Impor Gula Mantan Menteri Perdagangan Thomas Trikasih Lembong - Herang, Andika Rayhan Putra (Universitas Pendidikan Nasional, 2025)
This study aims to analyze the criminal elements in the alleged corruption case involving former Minister of Trade Thomas Trikasih Lembong regarding the issuance of raw sugar import quotas during 2015–2016. Using a normative juridical approach and qualitative analysis method, this research examines the legal aspects of sugar import policies suspected of violating regulatory procedures and causing state financial losses. The focus lies in establishing abuse of power that meets the criminal elements outlined in Article 2 and Article 3 of Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 on the Eradication of Corruption. The study also considers the principle of legality and general principles of good governance as the basis for evaluating whether administrative actions potentially constitute criminal offenses. The findings indicate that proving malicious intent (mens rea) and causal links to state losses are critical elements in classifying the actions as criminal corruption. This research contributes academically by clarifying the boundary between policy errors and criminal acts in the context of public officials’ accountability.